PO 8446 Collaborative tuberculosis research agenda at KEMRI center for global health research, kisumu, kenya. (24th April 2019) - Wandiga, Steve; Agaya, Janet; Gurrion, Ouma S; Okumu, Ochieng Albert; Kiringa, Grace; Otieno, Juliana; Mwai, Geoffrey; Nduba, Videlis; Munga, Stephen
Abstract : Background: Developing countries grapple with inadequate funding amidst high burden of diseases. Africa is home to 9 of the 22 countries with a high tuberculosis (TB) burden and to 29 of the 41 countries with a high TB-HIV burden. Kenya is among the high TB and high TB-HIV burden countries. The Western Kenya region has the highest burden of TB and HIV. North-South partnerships are pivotal in ameliorating funding gaps in clinical research. Methods: While optimising existing infrastructure and organising programme support (i.e sensitisation and awareness creation, leading to study participant recruitment), from 2005 to date we conducted with multiple North-South collaborators capacity strengthening, TB prevalence survey, observational studies, operational research, and vaccine and drug trials. Results: TB prevalence survey showed 600 cases per 100, 000 population, TB epidemiological studies among adolescents and infants yielded 680 and 900/100, 000 population respectively while 2 TB vaccine trials among infants and adults were conducted in Siaya. Three TB drug trials and a TB patient observational cum bio-bank study were concluded in Kisumu. KEMRI TB laboratory was upgraded from BSL2 to BSL3, was ISO-accredited in 2013, renewed in 2015 and 2017 and supports TB programme health facilities with retreatment specimens, supervision and mentorship. Over 25 operational TB studies grouped into community and case detection (increasing case detection), diagnostic and molecular (new diagnostic methods) and epidemiology studies (testing and monitoring cohorts for epidemiological questions) were implemented. Five PhDs, 9 Master's, 2 Postgraduate Diplomas, 6 Bachelor's degrees and 10 Diplomas have been supported. Siaya clinical research center was built while in Kisumu an adolescent clinic was constructed. This work involved 18 northern and 26 southern partners. Over 35 publications have been published out of these collaborations. Conclusion: North-South collaborations provided funding, expertise and resources to harness research capacity of KEMRI; hence the need to foster a global networking culture.